Caminho das ruas, caminho das pedras: sinais de alegria nas violências contra moradoras de rua em São Paulo - Santos, Lívia Maria Camilo dos (2021)
This work portrays part of field research carried out in São Paulo during my doctoral studies, from 2015 to 2020, with women who share the experience of living on the streets, in shelters or in occupations. The involvement with these women was held across three different territories, but with a common circumstance, which is having the street as a place of residence (permanent or temporary). Thus, our meetings and the sharing of experiences occurred at the Inclusion Center for Art, Culture, Work and Education (Cisarte); at the occupation Tia Estela, in the Viaduto Alcântara Machado and with the collective SP Invisível. Other meetings occurred in an autonomously way, on the sidewalks of the city center, where many women live. The field research was inspired by the ethnographic methodology, focusing on methodological principles that flowed during the research, which are: ethical-political listening; the virtues of caution and the identification of fields of sensitivity. The research aimed to find the strategies of resistance of women on the streets, paying attention to those affections that Espinosa would call useful - those of joy - since they contribute to the permanence in existence with dignity. Furthermore, supported by the concept of ethical-political suffering, we seek to understand the exclusion / inclusion dialectic as a producer and reproducer of affections, without avoiding historical and social conditions. We discovered some networks of violence that, most of all, are part of the daily lives of these women and we systematized them so we could cluster and better understand how these fetters are produced and what are the ways to break them. Thereby, we list: 1- the violations of rights that happen in the equipment destined to the care of the homeless population, seeking to understand how social protection is being processed in this place. 2- The violence that has occurred against the female body in the family environment since the previous domestic violence that leads them to the street situation. And we continue to denounce a common, but very perverse practice on the part of the judiciary, which is the destitution of the family power of the mothers who live on the street. 3- The analysis of this network of violence also brought the agenda for the hostile relationships that occur between women and their partners and between themselves; who often clash over territories, men, food, clothing, money. In this part, we emphasize a patriarchal logic of society that generates, feeds and reiterates competitions and disputes. In the end, but not at the end (as the struggle continues) we come to the path of bursting affections of active joys that are manifested among them. The research shows us that there are moments when these affections are generated in the colloquial meetings between their powerful bodies and eager for life for themselves and theirs. Situations that clearly deconstruct preconceived ideas of the street situation as a struggle just to get out of material precariousness. On the contrary, on the street, women cry out for their specific aesthetic, just like any other woman, in any other social class. She decides, for example, not to take an outfit for donation because she did not find it beautiful, because it wouldn´t fit well in her body. They find themselves in times of great disasters to talk about their lives, their daughters and sons, their loves and their strategies for fighting. And it is with this analysis of the affective constellation that is punctuated with powerful joys that we seek to illuminate the writing of this work, with the constant care of not incurring in fatalisms and in the total absence of affections useful for the maintenance of life. Right there, where the State distills all its neglect